The Relationships Between Student Ratings and Instructor Behavior: Implications for Improving Teaching - Cranton, Patricia A.; Hillgartner, William (Canadian Journal of Higher Education, 1981)
Although students' ratings of instruction have been examined in detail by educational researchers, the relationship between ratings and actual classroom behavior has not often been investigated. This study explores the relationship between student ratings and classroom observations. Twenty-eight professors from a wide range of academic disciplines participated in the study. Mean student ratings and frequencies of behavior in several categories were obtained for each professor. It was found that instructor behavior significantly predicted student questionnaire responses in three general areas. (1) When instructors spent time structuring classes and explaining relationships, students gave higher ratings on logical organization items. (2) When professors praised student behavior, asked questions and clarified or elaborated on student responses, ratings on the effectiveness of discussion leading were higher. (3) When instructor time was spent in discussions, praising student behavior, and silence (waiting for answers), students tended to rate the classroom atmosphere as being one which encourages learning.